Effects of drop height and surface instability on neuromuscular activation during drop jumps - Lesinski, Melanie; Prieske, O.; Beurskens, Rainer; Behm, D. G.; Granacher, U. (Scandinavian journal of medicine & science in sports, 2017)
The purpose of this study was to examine whether drop height-induced changes in leg muscle activity during drop jumps (DJ) are additionally modulated by surface condition. Twenty-four healthy participants (23.7 ± 1.8 years) performed DJs on a force plate on stable, unstable, and highly unstable surfaces using different drop heights (i.e., 20 cm, 40 cm, 60 cm). Electromyographic (EMG) activity of soleus (SOL), gastrocnemius (GM), tibialis anterior (TA) muscles and coactivation of TA/SOL and TA/GM were analyzed for time intervals 100 ms prior to ground contact (preactivation) and 30-60 ms after ground contact [short latency response (SLR)]. Increasing drop heights resulted in progressively increased SOL and GM activity during preactivation and SLR (P < 0.01; 1.01 ≤ d ≤ 5.34) while TA/SOL coactivation decreased (P < 0.05; 0.51 ≤ d ≤ 3.01). Increasing surface instability produced decreased activities during preactivation (GM) and SLR (GM, SOL) (P < 0.05; 1.36 ≤ d ≤ 4.30). Coactivation increased during SLR (P < 0.05; 1.50 ≤ d ≤ 2.58). A significant drop height × surface interaction was observed for SOL during SLR. Lower SOL activity was found on unstable compared to stable surfaces for drop heights ≥40 cm (P < 0.05; 1.25 ≤ d ≤ 2.12). Findings revealed that instability-related changes in activity of selected leg muscles are minimally affected by drop height.
Gesehen am 14.04.2020
First published: 26 July 2016